Learning from African American Lesbian Mothers about Conducting Research. Issue 3 (3rd October 2020) - Radis, Brie; Sands, Roberta G.
Abstract: The aim of this article is to convey lessons learned from a recent research study on Black lesbian, parented, partnered mothers and their families' experiences, lessons that challenge the cisheteronormative methodology for family studies and conducting research. Methodological barriers, including the researcher's white identity, language usage, and the political context, are used as examples of challenges gaining access to potential research participants. The research participants voiced ideas about how to provide sensitive, safe, and inclusive research that focuses on the unique perspectives of queer families. Discussions with these families underscore the importance of researcher reflexivity and partnering with individuals from the groups one wishes to work with to derive unique methods for collecting data. In this article the researcher is regarded as positioned as both insider and outsider and between these two positions. The examples outlined in this article draw attention to the plurality of queer families' experiences and the need for intersectional methodologies. Suggestions for future research include the creation and examination of social justice-oriented methodology through which African-American-parented queer families' experiences can be better understood.